The challenges of pre-calculus in times of change - Pilotti, Maura A. E.; Eltoum, Russina A.; Abdelsalam, Hanadi M.; Waked, Arifi (International Journal of Evaluation and Research in Education (IJERE), 2025)
Sustainable science, technology, engineering, and mathematics (STEM) education rests not only on gender equity in educational opportunities but also on the academic attainment of female students. In Saudi Arabia, women enrolled in engineering and computer science are both newcomers and a minority. The present study compared the performance of female undergraduate students in pre-calculus (a prerequisite for STEM programs) before and after the pandemic. It also examined changes in students’ perceived difficulty and value of pre-calculus, the stress experienced in it, and their determination to pursue STEM. In this study, pre-calculus performance declined after the pandemic. Furthermore, the course was perceived as more difficult and stressful, as well as less valuable. Nevertheless, students’ determination to continue in STEM was undeterred. After the pandemic, students reported mostly utilitarian motives for pursuing STEM degrees (i.e., career opportunities), and concerns about their ability to balance work and personal lives in STEM professions. The key challenge was a personal issue (i.e., balancing professional and personal lives) rather than a social issue (e.g., the persistent gender imbalance in STEM fields). These findings suggest that interventions supporting intrinsic motivation are key to students’ engagement and persistence in academic pursuits and thus to their ability to be academically and professionally successful in STEM.